Clinical-diagnostic signs of schizophrenia, comorbid with chronic somatic pathology. - Y. V. Oprya (Medičnì Perspektivi)
In order to determine the clinical and psychopathological signs of schizophrenia, combined with somatic disorders,186 schizophrenic patients (50 schizophrenic patients with cardiovascular diseases; 42 schizophrenic patients with diabetes type 2, 44 schizophrenic patients with obesity and 50 schizophrenic patients without chronic somatic diseases) were examined. As a research tool the clinico-psychopathological method (analysis of medical history, complaints and condition of the patient) was used, which was supplemented by the scale of positive and negative symptoms (PANSS). In the course of the study, a frequency analysis of socio-demographic data, general clinical characteristics of the endogenous process, as well as features of clinical and psychopathological manifestations of schizophrenia in patients with these somatic diseases were performed in accordance with the procedure of consistent statistical analysis. Specific diagnostic clinical-psychopathological sign-risk markers and anti-risk combinations of schizophrenia with marked variants of somatic disorders have been identified: the duration of psychotic disorder more than 15 years; the presence of depressive symptoms of moderate and higher severity; anxiety higher than moderate; hypochondria ideas of moderate and higher degree; abuse of psychoactive substances in history and emotional alienation above the weak level of expressiveness were established: as the most informative signs of the risk of cardiovascular disorders. The reliable differentiation of the risk of diabetes mellitus type II in patients with schizophrenia is provided by the following features: lack of professional employment; presence of symptoms of moderate and higher levels of excitation; duration of psychotic disorder more than 15 years; and disturbance of attention to a moderate and higher degree of expressiveness. The most informative signs of the risk of obesity in schizophrenia are: lack of professional employment; social isolation; the presence of passive-apathy social isolation of moderate and higher severity.